Efficacy of Narrow Band Imaging in Detecting Lower Gi Lesions and Its Histologic Correlation - moin, Mohammad; Anees, Afzal; Saeed, Noora; Akhtar, Kafil (Annals of Pathology and Laboratory Medicine, 2018)
Background: To evaluate the efficacy of Narrow band imaging (NBI) in detecting lower GI lesions and differentiation on the basis of color, vascular pattern and surface pattern findings on NBI with histopathologic correlation. Material and Methods: 94 patients of both gender, with lower GI symptoms were subjected for lower GI endoscopy by conventional white light endoscopy and CLV-190 HD colonoscope having Narrow-band imaging (NBI) as standard feature after obtaining an informed consent. Patients who did not give consent, patients with severe inflammatory bowel disease and who lost during follow up were excluded from the study. All NBI findings of suspected lesions were classified according to NICE (NBI International Colorectal Endoscopic) classification, into hyperplastic lesion, adenomatous and invasive carcinoma. Biopsies were taken and stained with Haematoxylin and Eosin as well as Periodic Acid Schiff stain. Statistical analysis was done to compare NBI diagnosis with the histopathological diagnosis. Results: Majority of the patients were in the third decade of life, with a mean age of 36.22 years. Diarrhea was the commonest clinical presentation, in 60 (63.8%) patients. NBI was suggestive of ulcerative colitis/Inflammatory bowel disease (IBD) in 59 (62.8%) patients, neoplastic polypoidal lesion in 24 patients (25.5%) and polypoidal non-neoplastic lesion in 11 (11.7%) patients. Out of 59 (62.8%) cases of Ulcerative colitis (UC), 35 (37.2%) were polypoidal, among which 24 (68.6%) were suggestive of neoplastic polypoidal lesion (NICE II-III) and 11(31.4%) were non-neoplastic polypoidal lesion (NICE I). Out of 59 cases of UC, clear mucosal vascular pattern (MVP) was found in 11 (18.6%) cases and obscure MVP in 48 (81.4%) cases. Conclusions: NBI provides a unique image with contrast enhancement and can emphasize the capillary pattern and surface architecture and plays a major role in the differentiation of neoplastic and non-neoplastic colorectal lesion, with high sensitivity and specificity.